Curriculum in the Eyes of Future Educators: A Metaphor Analysis from First-Year Pre-Service Science Teachers - Charlos Falentino; Evanita Mutang; Abdul Hakim; Nurul Fitriyah Sulaeman; Atin Nuryadin (South Sulawesi Education Development (SSED), 2025)
First-year science pre-service teachers are a vital future generation dealing with various education systems, not least of which is the curriculum. This study aims to understand how first-year science pre-service teachers perceive the curriculum. This qualitative study probes those conceptions through metaphor analysis of responses from 104 Indonesian first‑year science pre‑service teachers. Participants supplied a single metaphor and a brief rationale; 57 unique metaphors survived screening and were grouped into five conceptual categories—Guidance, Foundation, Dynamism & Adaptability, Essential & Sustaining, and Complexity & Challenge. The most frequent metaphors included water, map, and sun, signalling an overall optimistic and functional view of the curriculum. While most metaphors framed the curriculum positively—as an indispensable guide or life‑support system—some acknowledged its intricacy and the effort required to navigate it. Findings suggest that optimism may stem from limited first‑hand experience with curriculum implementation, contrasting with practising teachers who often regard curriculum change as problematic. The implications of this study for teacher education programs include the need to foster critical and practical curriculum literacy from the start of training. In addition, by mapping how pre-service science teachers in Indonesia structure their curriculum, this study provides teacher education programs with a concrete reference point to prepare them for the tumultuous curriculum changes they will face as professional teachers.